2017
DOI: 10.18632/oncotarget.18737
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-derived exosomes promote lung cancer metastasis by increasing MMP9 activity via transferring MMP3 to lung cancer cells

Abstract: Obesity is involved in tumor progression. However, the corresponding mechanisms remain largely unknown. Here, we report that adipocytes increase the invasive ability of tumor cells by producing exosomes with a high level of MMP3. Compared with 3T3-L1 cells, 3T3-L1 adipocytes are enriched in MMP3 protein and can transfer MMP3 to 3LL lung cancer cells. Then, MMP3 activates MMP9 activity in 3LL cells and promotes invasion in vitro and in vivo via MMP9. Furthermore, MMP3 protein levels in lung tumor tissues from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 40 publications
1
49
0
3
Order By: Relevance
“…Relevantly, EVs derived from 8701-BC breast cancer cells and HT-1080 fibrosarcoma cells were reported to contain MMP9 in both pro-and mature forms with proteolytic activity [45,46]. Besides, MMP3 has been identified in/on EVs released from stromal cells, such as mesenchymal stromal cells (MSC) and adipocytes [47,48]. Moreover, it has been shown that cancer exosomes could trigger MSC differentiation into pro-angiogenic and pro-invasive myofibroblasts, secreting high levels of matrix-regulating factors (MMP-1, -3, and -13), VEGF-A, and HGF [49].…”
Section: Discussionmentioning
confidence: 99%
“…Relevantly, EVs derived from 8701-BC breast cancer cells and HT-1080 fibrosarcoma cells were reported to contain MMP9 in both pro-and mature forms with proteolytic activity [45,46]. Besides, MMP3 has been identified in/on EVs released from stromal cells, such as mesenchymal stromal cells (MSC) and adipocytes [47,48]. Moreover, it has been shown that cancer exosomes could trigger MSC differentiation into pro-angiogenic and pro-invasive myofibroblasts, secreting high levels of matrix-regulating factors (MMP-1, -3, and -13), VEGF-A, and HGF [49].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are extracellular microvesicles (30 to 150 nm in diameter) derived from various cells, transferring different proteins, non-coding RNA and coding RNA, which have been looked as diseases biomarkers or cellcell communication factors [31,32]. Increasing studies have unveiled that exosomes derived from the insulinresistant adipocyte were implicated in the skeletal muscle insulin resistance, obesity-related liver disease, atherosclerosis, and lung cancer [33][34][35][36]. Given the broad spectrum of the discoveries of the function of these exosomes, it is not surprising that exosomes derived from insulin-resistant adipocytes, functioned as independent metabolic units, which might provide a promising therapeutic target on the insulin resistance, diabetes, and related metabolic disorders [37].…”
Section: Discussionmentioning
confidence: 99%
“…These exosomes, either TDEs or non‐TDEs, are also heterogenetic, differing in size, morphology, composition or biogenic mechanisms; moreover, they are able to generate a complex network of interactions that are both tumor facilitative and inhibitive . For instance, non‐cancer cells, such as adipocytes, could transfer matrix metalloproteinase (MMP)3 proteins via exosomes, which fused with tumor cells enhance their invasive ability by activating MMP9 . Acute myeloid leukemia blasts remodel the bone marrow niche into a leukemia‐growth‐permissive and normal‐hematopoiesis‐suppressive microenvironment via TDEs, thus promoting leukemic cell proliferation and survival, while suppressing normal hematopoiesis .…”
Section: Exosomes In Sequential Processes Of Tumor Metastasismentioning
confidence: 99%
“…2 For instance, noncancer cells, such as adipocytes, could transfer matrix metalloproteinase (MMP)3 proteins via exosomes, which fused with tumor cells enhance their invasive ability by activating MMP9. 15 Acute myeloid leukemia blasts remodel the bone marrow niche into a leukemia-growth-permissive and normalhematopoiesis-suppressive microenvironment via TDEs, thus promoting leukemic cell proliferation and survival, while suppressing normal hematopoiesis. 16 Here, we highlight five different crucial events in primary tumor sites, hoping to define the specific roles of exosomes in the initiation of metastasis.…”
Section: Exosomes In Sequential Processes Of Tumor Metastasismentioning
confidence: 99%